PENGUATAN KARAKTER SISWA MELALUI PEDAGOGIK REFLEKTIF PROFETIK DI SEKOLAH DASAR: ANALISIS LITERATUR TERHADAP IMPLEMENTASI DAN INTERNALISASI NILAI KENABIAN - Purnama, Nalis; Sauri, Sofyan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the strengthening of elementary school students' character through the integration of reflective pedagogy and prophetic education based on a literature review. The research employs a qualitative approach using a library research method by examining 17 relevant scientific articles. Data were collected through a systematic search using Google Scholar supported by the Publish or Perish application, while data analysis was conducted using thematic analysis techniques. The findings reveal that student character development is consistently influenced by three main pillars: teacher role modeling, internalization of religious and prophetic values, and reflective pedagogical approaches. Teacher role modeling serves as a dominant factor in shaping students’ character by providing concrete behavioral examples. Meanwhile, value internalization establishes moral and spiritual foundations, and reflective learning deepens students’ understanding through meaningful experiences. Furthermore, prophetic value-based education proves to be a comprehensive approach in fostering holistic character development by integrating moral, social, and spiritual dimensions. However, the study also identifies an imbalance in value implementation, where religious aspects are more dominant than affective values such as empathy and patience. Therefore, the integration of reflective and prophetic pedagogy is considered a relevant and strategic approach to address contemporary educational challenges, particularly in the digital era. This study recommends the implementation of more contextual, reflective, and sustainable learning practices to optimize students’ character development comprehensively.